Proposed strategies for improving tax collection vehicle Cundinamarca Department (2013)
The Finance team of Cundinamarca has within its objectives attend the management of incomes and public outlay, the policy of financing, consolidation and good handle of public finances. Its principal duties are formulated and develop, under Governor's Orientation, tax policy in order to control tax evasion; regarding to public credit, they created a budget of incomes and outlays: treasury and raising funds investment in accordance with the Constitution, the law and the ordinances. Vehicle Tax is part of the taxes and revenues of the Department which manages and oversees the Finance team - Direction of Tax and revenue management, this tax is generated by the ownership or possession of encumbered vehicles, and will be paid by the owner or registered keeper of the vehicle at traffic units of the Department of Cundinamarca. This tax has permanent fluctuations with downward trend, and this is generated because of the absence of new vehicle registrations, the aging of existing and services provided in the Finance team, Direction of Tax and revenue management doesn’t satisfy needs and expectations. A diagnosis made with the behavior of the tax and the causes which influence on this negative behavior and the collection, then outline strategies to improve positively the collection, and set up the projections made by the Finance team, focusing on excellent care to the taxpayer and therefore in meeting the objectives of the Development plan "Cundinamarca Life Quality"